ACTIVITY-BASED COSTING (ABC) SYSTEM TO DETERMINE PRODUCTION COST (STUDY ON CV TWIN ALFA) - Aprilia Wulandari; Atika Violeta Hanum; Talitha Rahmi Ardiyanti; Puji Handayati; Makaryanawati (Halu Oleo University, 2024)
This study explores the implementation of the Activity-Based Costing (ABC) system at CV Twin Alfa, a company engaged in the production of automotive training equipment for vocational and mechanical engineering students. In an increasingly competitive market, the necessity for accurate cost information is paramount for strategic decision-making and pricing strategies. Traditional cost accounting methods, which allocate manufacturing overhead based solely on production volume, lead to significant inaccuracies in cost calculations, particularly for companies with diverse product offerings. This research demonstrates that the ABC system provides a more precise method for calculating production costs by linking expenses directly to the activities that generate them. Findings indicate that employing the ABC system not only enhances the accuracy of cost information but also supports improved operational efficiency and competitive pricing. The study concludes that adopting the ABC approach is essential for CV Twin Alfa to refine its cost management practices and maintain a competitive edge in the marketplace.